Penggunaan media kartu huruf dan kata untuk mengatasi kesulitan membaca permulaan di kelas II sekolah dasar - Suzia Ulhaq; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Universitas Sebelas Maret, 2025)
This study aims to overcome the initial reading difficulties of grade II students of SDN Karangasem 4 Surakarta in the 2024/2025 academic year by using letter and word card media. This study is a type of Penelitian Tindakan Kelas (PTK) which is carried out in two cycles, with two meetings in cycle I and one meeting cycle II. The sources of research data include the use of letter and word card media by teachers and aspects of students’ initial reading abilities. Data collection techniques are carried out through observation, interviews, performance tests, and documentation. The results of the study indicate that the use of letter and word card media can overcome students’ initial reading difficulties. The average reading ability at the first meeting of cycle I reached 73.8, at the second meeting of cycle I it reached 81.4, and in cycle II it increased to 84.5. This study concludes that the use of letter and word card media cand overcome the initial reading difficulties of grade II students of SDN Karangasem 4 Surakarta.